Causes and Consequences of Species Diversity in Forest Ecosystems - Gilliam, Frank S. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
What are the causes and consequences of species diversity in forested ecosystems, and how is this species diversity being affected by rapid environmental and climatic change, movement of invertebrate and vertebrate herbivores into new biogeographic regions, and expanding human populations and associated shifts in land-use patterns? In this book, we explore these questions for assemblages of forest trees, shrubs, and understory herbs at spatial scales ranging from small plots to large forest dynamics plots, at temporal scales ranging from seasons to centuries, in both temperate and tropical regions, and across rural-to-urban gradients in land use.